2010
DOI: 10.2527/jas.2009-2486
|View full text |Cite
|
Sign up to set email alerts
|

Corn or sorghum wet distillers grains with solubles in combination with steam-flaked corn: In vitro fermentation and hydrogen sulfide production1

Abstract: The effects of wet distillers grains with solubles (WDG) on in vitro rate of gas production, IVDMD, H(2)S production, and VFA were evaluated. Five substrate treatments that were balanced for ether extract content were arranged in a 2 x 2 + 1 factorial. Factors were concentration (15 or 30%; DM basis) and source of WDG (corn or sorghum WDG; CDG and SDG, respectively) plus a 0% WDG control in substrates with steam-flaked corn as the basal grain. Control substrates had greater (P < 0.01) IVDMD and total gas produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
9
14
4
Order By: Relevance
“…The CON and 12.5% WDGS substrates were intermediate. In contrast to our results, with high-concentrate substrates, May et al (2010b) reported that as either WDGS from corn or sorghum increased from 0 to 15 to 30% (DM basis), IVDMD decreased. Similar to our results, however, Quinn et al (2010) reported a tendency for a linear increase in IVDMD with WDGS from sorghum, but no effect on IVDMD with WDGS from corn.…”
Section: In Vitro Fermentation Results-experimentscontrasting
confidence: 99%
“…The CON and 12.5% WDGS substrates were intermediate. In contrast to our results, with high-concentrate substrates, May et al (2010b) reported that as either WDGS from corn or sorghum increased from 0 to 15 to 30% (DM basis), IVDMD decreased. Similar to our results, however, Quinn et al (2010) reported a tendency for a linear increase in IVDMD with WDGS from sorghum, but no effect on IVDMD with WDGS from corn.…”
Section: In Vitro Fermentation Results-experimentscontrasting
confidence: 99%
“…Data from the current study are consistent with those of Quinn et al (2010a,b), in which no differences in IVDMD were noted for substrates con-taining either 15 or 30% corn DG (DG sources similar in composition to the current study). The results of the present study are not supported, however, by those of May (2010) or May et al (2010b), in which increasing DG in substrates led to decreased IVDMD. In vivo measurements of apparent total tract DM digestion with 25% DDG in diets (Uwituze et al, 2010) were not affected by roughage source, but were decreased by DDG inclusion.…”
Section: Expcontrasting
confidence: 99%
“…Similar estimates of V for different DG concentrations in substrates is not supported by results of Quinn et al (2010a,b), where substrates with 15% DG had greater total gas production than those with 30% DG. Neither DG nor roughage source affected (P = 0.58) lag time of gas production, which is consistent with the results of May (2010) and May et al (2010b).…”
Section: Expsupporting
confidence: 89%
“…Further evaluation of the postruminal and ruminal digestion of nutrients, particularly starch and fiber, in diets containing WDG is needed. In a companion study to the present experiment, May et al (2010) estimated IVDMD of substrates containing 15 or 30% SDG or CDG compared with a control substrate without WDG. Including WDG in the substrate decreased IVDMD, and substrates containing 15% WDG were more digestible than those containing 30%.…”
Section: Expmentioning
confidence: 98%